2003
DOI: 10.1007/s00330-002-1798-z
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous adenocarcinoma arising from fistula-in-ano: findings on MRI

Abstract: Sir,We report on a case of mucinous adenocarcinoma arising from a fistula-in-ano, which formed a huge subcutaneous mass in the buttock.A 68-year-old diabetic man was referred to our hospital. Two years prior to the admission, the patient had first recognized a small subcutaneous nodule which gradually increased in size. On admission, he complained of a spontaneous pain. The mass measured 12×7 cm, and the covering skin had some ulcers with a foul smell.A contrast-enhanced transverse T1-weighted MR image (Fig. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…However, the patient survived for 3 years, developing fistula recurrence but not distant metastases. So, in this case, we can conclude that tumour progression was slower than that observed in squamous cell carcinoma [1,2].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the patient survived for 3 years, developing fistula recurrence but not distant metastases. So, in this case, we can conclude that tumour progression was slower than that observed in squamous cell carcinoma [1,2].…”
Section: Discussionmentioning
confidence: 82%
“…Surgical resection is the first priority of curative treatment [1][2][3], whereas radiotherapy alone or with chemotherapy can be an adjuvant therapeutic option with favourable prognosis [3][4][5]. Below, we present a case of mucinous perianal carcinoma successfully treated by surgical resection alone.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of mucinous adenocarcinomas typically show low-signal intensity on T1-weighted and a markedly high-signal intensity on T2-weighted MR images [6]. A previous report suggested that a fistula between the mass and the anus is a characteristic finding of mucinous adenocarcinoma arising from fistula in ano [7]. It has been suggested that markedly hyperintense content on T2-weighted images reflects the mucin pool of mucinous adenocarcinomas [6].…”
Section: Discussionmentioning
confidence: 95%
“…19 Diagnosis can be based on the following three characteristic fi ndings on magnetic resonance imaging: hyperintense fl uid on T2-weighted images; enhanced solid components; and a fi stula between the mass and the anus. [20][21][22] Histological examination of the resected specimen from this patient revealed clusters of cancer cells fl oating in a mucous lake, which explained the diffi culty in obtaining cancer cells by needle biopsy (Fig. 4a-c).…”
Section: Discussionmentioning
confidence: 96%